‘A Mulligan’s stew’: educational preparation for today’s academic library liaisons in the humanities and social sciences - Fleming-May, Rachel; Bishop, Wade; Villarreal, Caroline (Information Research an international electronic journal, 2025)
Introduction. This short paper reports on findings from a survey of academic librarians with liaison responsibilities to college and university social sciences and humanities departments, with particular attention to newer responsibilities related to research data management and scholarly communications, areas less commonly associated with humanities and humanistic social sciences liaison work. Method. The survey was distributed to 1085 individuals, 330 of whom responded (rate: 30.4%). Analysis. This paper reports on one segment of the survey’s findings: the extent to which respondents believe their American Library Association (ALA)-accredited master’s degree and, where applicable, additional graduate coursework, prepared them for specific duties associated with liaison work. Results. Three findings are discussed: 1) impressions about the ALA-accredited master’s from respondents who have not participated in other graduate education 2) as compared to respondents who have completed additional graduate education, and 3) respondents’ impressions of the extent to which additional graduate study prepared them for liaison work as compared to the preparation afforded by the ALA-accredited master’s. Conclusions. Respondents do not believe the ALA-accredited master’s to have provided strong preparation for the ‘Mulligan’s Stew’ of tasks, skills, and responsibilities associated with liaison work. The Discussion and Conclusion sections share suggestions for strengthening liaison preparation.